A rare life-threatening rectus sheath haematoma in post lower segment cesarean section patient: a case report - Chavan, Niranjan; Kampoowale, Shreya; Ammara, Umme; Sakhalkar, Ashwini; Kapote, Deepali (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Rectus sheath hematoma is a rare but potentially life-threatening complication following any major abdominal surgery. The nonspecific nature and lower incidence of this disorder may cause a delay in the diagnosis, and can often be misdiagnosed as a cause of acute abdomen. A rectus sheath hematoma consists of blood accumulating between the rectus abdominis muscle and the rectus sheath. It is most frequently due to a hemorrhage from the superior or inferior epigastric artery or any non-specific bleeder or a direct tear in the muscle itself. It has many specific risk factors such as local trauma, coagulopathies, anticoagulant use, severe coughing, hypertension, and peripheral vascular disease. In this case, the patient presented with rectus sheath hematoma following cesarean section on the 10th post-operative day. She presented with a history of fall followed by lower abdominal pain. Clinical suspicion and ultrasonography were used to confirm the diagnosis and the patient was managed with exploration and hematoma drainage. Its early diagnosis and management helped to prevent hazardous complications.